Good governance in rural development : country specific issues and experiences, proceedings of the COMSEC-BARD organised International Training Course on Good Governance in Rural Development 20 April - 20 May 2008 - Bangladesh Academy for Rural Development; Kashem, , Mohammed Mir; Karim, Abdul; parvin, Iran (Dhaka : Bangladesh Academy for Rural Development, 2008)
Chiefly with reference to South Asia.
"Sponsored by Commonwealth Secretariat; organized by BARD"--Cover.
Includes bibliographical references.
Keywords: Rural development -- South Asia -- Congresses; Political participation -- South Asia -- Congresses